A comparative study on the evolution of left wings, right wings and pivots at male handball teams H.C.M. Constanta and F.C. Barcelona in "Champions League" 2011-2012 - Curitianu, I.; Neamtu, M. (Procedia - Social and Behavioral Sciences, 2014)
The research had as object of study the recording of the evolution of players activating on the left wing, right wing and pivot position in teams H.C.M. Constanta and F.C. Barcelona in the competition "Champions League" 2011-2012 in terms of the technique and tactics that these players use in the attack compartment of the handball game. We chose to analyze male team H.C.M. Constanta because it is the only team that represents Romania in the competition Champions League and team F.C. Barcelona from Spain that achieved good results in this competition throughout the years. In terms of individual technique and tactics, the players from team H.C.M. Constanta showed a good percentage at the 7m throws, but F.C. Barcelona players had better efficacy due to the high experience, this team going through high-level competitions in the same formula. From this analysis we were able to draw clear conclusions on the potential of the players that activate in team H.C.M. Constanta and to establish proposals for improving both the technical and tactical evolution of these players, but also the manner in which they cooperates with their teammates in solving situations resulting from the game.